The Influence of Extraction Method (Solvent Extraction with Hexane vs. Steam Distillation) on the Composition of Essential Oils from Lemon Peels Analyzed with FTIR (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The extraction method selected for extracting essential oils from lemon peels has a marked impact on both the yield and the chemical composition of the resulting product. In this study, the chemical profiles of the oils extracted with solvent extraction using hexane and steam distillation, which are commonly used extraction methods were analyzed via Fourier Transform Infrared Spectroscopy (FTIR) and compared. The findings demonstrate that hexane extraction preferentially recovers non-polar constituents, such as alcohols, phenols, and aromatic compounds. In contrast, steam distillation is more effective at isolating volatile and aliphatic hydrocarbons, particularly limonene and related terpenes, which are significant for their characteristic citrus aroma. The FTIR spectra showed the characteristic existence of certain functional groups such as alkanes, alkenes, carbonyls, and aromatics that enabled distinction between the compositions of the essential oils from the two extraction processes. The results emphasize the importance of the choice of the extraction process, particularly in the case of designing essential oil compositions for targeted purposes in the food, pharmaceutical, or cosmetic industry. In general, these results offer valuable guidance on how methods for extraction could potentially be modified to more closely match the intended results.